Experimental Study on Prevention of Coal and Gas Outburst by Hydraulic Fracturing in High Gas Coal Mine in Yangquan Mining Area - Zhou Zhang; Pengxiang Wang; Wanying Yu; Lifang Zhao; Yunxing Cao; Baoan Xian; Yibing Wang; Fei Zhang (Energy Science & Engineering)
ABSTRACT To investigate the hydraulic fracturing mechanism of high‐fluid wells in the Yangquan mining area, coal seams from the Xinyuan and Xinjing mines were selected as research subjects. Experiments were conducted using the TCQT‐III low‐permeability coalbed gas‐phase displacement and production enhancement apparatus, along with the FINESORB‐3120 isothermal adsorption instrument. The study included hydraulic fracturing simulation tests, experiments on the effects of water content on the physical and mechanical properties of coal, and analyses of gas adsorption and desorption responses to external water. Experimental results indicate that after hydraulic fracturing simulation, the water content and permeability of coal samples increased by 3.97–6.79 times and 33.45–75.61 times, respectively, compared to their original state. The observed deformations during fracturing suggest the connectivity and expansion of microfractures within the coal. Under identical stress loading conditions, higher water content led to lower peak strength and greater deformation, with the maximum reduction in peak strength reaching 34.44%. During isothermal adsorption and desorption, the values of parameters a and b, as well as the desorption volume, consistently decreased with increasing water content, with b showing a maximum reduction of over 50%. A systematic analysis of these experimental results was conducted to explore the comprehensive outburst mitigation mechanism of high‐volume hydraulic fracturing. These findings provide valuable insights for applying hydraulic fracturing technology to mitigate outbursts in high‐gas mining areas.